The Impact of The Pandemic on The Quality of Asset Management – Analysis of The Effectiveness of Investments in Stocks of Medical Companies Listed on the WSE - Wioletta SKRODZKA (Communications of International Proceedings, 2021)
Objectives: The aim of the article is to determine the impact of the pandemic on asset management, including the effectiveness of investments in medical stocks. Background: The COVID-19 pandemic forced changes in the global economy. The focus of the entire world shifted on the medical sector. Their stocks were trading at high levels.  Stocks of biotechnology companies that produce coronavirus detection tests, disease-fighting drugs or vaccines reacted similarly. In this context, the evaluation of the effectiveness of investments in medical stocks seems justified from an asset management point of view. Expected Results: This paper focuses on the ways of defining effectiveness as a general concept, and from the standpoint of the theory of investment management. The investment effectiveness of the medical industry during the pandemic of 2019-2020 was analyzed on the example of investments in selected stocks of companies from the WIG- LEKI index listed on the Warsaw Stock Exchange. Returns on selected stocks and risk-adjusted measures of profitability based on the Capital Asset Pricing Model (CAPM) were used. A statistical verification of the quality of asset management in relation to the performance of the WIG index was carried out. The results show that during the pandemic the effectiveness of investments in the shares of the Polish medical industry differed significantly from the WIG investment portfolio. Implications: This type of information can be discounted in the asset management process.
Keywords: medical industry; investment effectiveness analysis; assets management